Analisa Pengaruh Variasi Penggabungan Asbuton dan Aspal Minyak Terhadap Campuran AC-BC - Haikal, Muhammad Fikry; Jasman; Widarto, Hendro (Jurnal Karajata Engineering, 2024)
Asbuton, which has a higher stability and softening point and also lower deformation is expected to be an alternative to overcome the weaknesses of asphalt concrete mixtures. Also cheaper operational costs are the selling point of asbuton that needs to be watch out for. The aim of this study was to determine the Optimum Asphalt Content or also known as KAO of the mixing between asbuton and asphalt in order to obtain a mixture composition that meet the AC-BC characteristics requirements. The research method used in this paper is the experimental method and analyzed in accordance with the General Specification of Bina Marga 2018 revision 2. Based on the results of research conducted in the laboratory of University of Muhammadiyah Parepare, the asphalt mixture with Asbuton LGA type 50/30 with a content of 7%, 8% and 9% KAO was obtained at 6.75%. From the three variations, AC-BC with the addition of 7% LGA has the best stability with a MQ value of 319.93 kg/mm